Development of a fluorescence aptasensor for rapid and sensitive detection of Listeria monocytogenes in food. (April 2021) - Liu, Rui; Zhang, Yunlian; Ali, Shujat; Haruna, Suleiman A.; He, Peihuan; Li, Huanhuan; Ouyang, Qin; Chen, Quansheng
Abstract: In this study, a simple fluorescence aptasensor was developed for rapid and sensitive detection of Listeria monocytogenes in food. The aptasensor was comprised of two parts. Aptamer-functionalized upconversion nanoparticles (UCNPs) recognized and adhered to the L. monocytogenes cells and provided strong fluorescent signals. Aptamer-functionalized magnetic nanoparticles (MNPs), which also recognized and adhered to the cells, were used to concentrate the aptamer-UCNP/ L. monocytogenes /aptamer-MNP complex. The fluorescence intensity was measured and calibrated to a concentration series of L. monocytogenes . A low limit of detection of 8 cfu mL −1 was estimated from the range of 68 to 68 × 10 6  cfu mL −1 . Compared with other methods currently available, the proposed method had wider detection range and higher sensitivity . Furthermore, the selectivity and functionality when used to detect L. monocytogenes in real food samples suggest it may be useful for practical applications. Highlights: A fluorescence aptasensor was successfully developed. Rapid and sensitive detection of L. monocytogenes was achieved. Application of the fluorescence aptasensor in food produced satisfactory results. Fluorescence aptasensors could be created for detecting other foodborne pathogens by changing the aptamer.